ANALISIS SITIRAN ARTIKEL ILMIAH MAHASISWA PROGRAM STUDI D3 PERPUSTAKAAN UNIVERSITAS UDAYANA 2017-2019 - Rispasanti Dewi A.S, Ni Putu Cindra; Ginting, Richard Togaranta; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT The purpose of this research is to find out the name of the author, journal and online website which are often cited, obsolescence of cited literature and the form of cited literature in the article of the students in D3 Library Study Program Udayana University who were graduates in 2017-2019. Using descriptive research with the data source is bibliography scientific articles as many as 46 scientific articles with 378 bibliographies. From the results of the study showed that the rank of authors who are frequently cited is Mr. Sugiyono as many as 29 times cited. In analyzing the journal as many as 66 citations. Journals that are often cited are journals from within the country. At the age of half-life, were 10 years old. In the research results, the analyzed forms of literature are namely books, journals, online websites, and laws. Keywords: Citation, Scientific Articles, Literacy obsolescence.